Effect of toothpaste with nano-sized trimetaphosphate on dental caries: In situ study - Danelon, Marcelle [UNESP]; Pessan, Juliano Pelim [UNESP]; Souza Neto, Francisco Nunes; Camargo, Emerson Rodrigues de; Botazzo Delbem, Alberto Carlos [UNESP] (Elsevier B.V., 2015)
Objectives: This in situ study was to evaluate the remineralizing effect of a fluoride toothpaste supplemented with nano-sized sodium trimetaphosphate (TMP).Methods: This blind and cross-over study was performed in 4 phases of 3 days each. Twelve subjects used palatal appliances containing four bovine enamel blocks with artificial caries lesions. Volunteers were randomly assigned into the following treatment groups: Placebo (without F and TMP); 1100 ppm F (1100), 1100 supplemented with 3% micrometric TMP (1100 TMP) and with nano-sized TMP (1100 TMPnano). Volunteers were instructed to brush their natural teeth with the palatal appliances in the mouth during 1 min (3 times/day), so that blocks were treated with natural slurries of toothpastes. After each phase, the percentage of surface hardness recovery (%SHR), integrated mineral recovery (IMR) and integrated differential mineral area profile (Delta IMR) in enamel lesions were calculated. F in enamel was also determined. Data were analyzed by ANOVA and Student-Newman-Keuls test.Results: Enamel surface became 20% harder when treated with 1100 TMPnano in comparison with 1100 (p < 0.001). 1100 TMPnano showed remineralizing capacity (IMR; Delta IMR) 66% higher when compared with 1100 TMP (p < 0.001). Enamel F uptake in the 1100 TMPnano group was 2-fold higher when compared to its counterpart without TMP (p < 0.001).Conclusion: The addition of 3% TMPnano to a conventional toothpaste was able to promote an additional remineralizing effect of artificial caries lesions.Clinical significance: Toothpaste containing 1100 ppm F associated with TMPnano showed a potential of higher remineralization to 1100 ppm F and 1100 ppm F micrometric TMP. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Toothpastes; Tooth remineralization; Phosphates; Nano-sized